Rates of clinically significant prostate cancer in African Americans increased significantly following the 2012 US Preventative Services Task Force recommendation against prostate specific antigen screening: A Single Institution Retrospective Study. Issue 2 (6th December 2019) - Arace, Jeffrey; Flores, Viktor; Monaghan, Thomas; Robins, Dennis; Karanikolas, Nicholas; Winer, Andrew; Weiss, Jeffrey
Summary: Purpose: We determined the impact of the 2012 US Preventative Services Task Force recommendation against prostate specific antigen screening on detection rates and biopsy patterns in African American and Caucasian patients. Materials and Methods: Demographics, PSA, transrectal ultrasonography volume and pathologic data were collected on patients who underwent their first ultrasound‐guided prostate biopsy between January 2007 and June 2018 at a New York City Veteran Affairs Hospital. Results: 609 biopsies were analysed preguideline (113 per year), and 487 were analysed postguideline (81 per year). There was no significant difference in the detection rates of low, intermediate or high grade PCa in Caucasians. In contrast, African Americans were significantly more likely to be diagnosed with PCa in the postguideline group (56% pre vs 66% post, P  = .016), and significantly more likely to be diagnosed with intermediate‐high grade PCa (38% pre vs 47% post, P  = .038). Before the 2012 USPSTF recommendation, African American and Caucasian patients undergoing their first biopsy were equally likely to be diagnosed with high‐grade PCa (11% AA vs 11% CA). After the 2012 decision, we found that African Americans were 50% more likely than Caucasians to be diagnosed with high‐grade PCa on first biopsy (10% AA vs 15% CA, P  = .008). Conclusions: In the 6 years following the 2012 USPSTF recommendation, detection rates of intermediate‐high risk disease remained unchanged for Caucasian patients but have increased significantly for African Americans. The results of our study strongly support the role of routine PSA screening, particularly in higher risk patients such as African Americans.